Aplikasi Android Contruct 2 untuk Media E-Learning pada Materi Peluang - Ridho, Fachri; Anggoro, Bambang Sri; Andriani, Siska (Desimal: Jurnal Matematika, 2019)
This study aims to produce an Android-based E-Learning learning media on opportunity material. This research method is Research and Development (R & D) based on Sugiyono's development model. The material expert's assessment of the learning media is included in the "Good" category with an average percentage of 79.05%. The media expert's assessment of the learning media is included in the "Very Good" category with an average percentage of 87.67%, the assessment of education practitioners on this learning media is included in the "Very Good" category with a percentage of completeness of 82.57%. In a small scale trial which was attended by 10 students in class XI obtained a percentage of 81.60%. Based on the results of the questionnaire responses that have been filled in by students, these results place the learning media on the criteria of "Very Interesting". Based on the results of a large-scale trial which was attended by 30 students of class XI, the percentage of 88.78% was included in the criteria of "Very Interesting", and the results of the testing of the effectiveness of learning media were 88.33% included in the criteria of "Very Effective".